Chemoresponse of de novo Acute Myeloid Leukemia to “7+3” Induction can Be Predicted by c-Myc-facilitated Cytogenetics - Hsiao, Tzu-Hung; Wang, Ren Ching; Lu, Tsai-Jung; Shih, Chien-Hung; Su, Yu-Chen; Tsai, Jia-Rong; Jhan, Pei-Pei; Lia, Cai-Sian; Chuang, Han-Ni; Chang, Kuang-Hsi; Teng, Chieh-Lin (Frontiers in Pharmacology, 2021)
Background: Identifying patients with de novo acute myeloid leukemia (AML) who will probably respond to the “7 + 3” induction regimen remains an unsolved clinical challenge. This study aimed to identify whether c-Myc could facilitate cytogenetics to predict a “7 + 3” induction chemoresponse in de novo AML. Methods: We stratified 75 untreated patients (24 and 51 from prospective and retrospective cohorts, respectively) with de novo AML who completed “7 + 3” induction into groups with and without complete remission (CR). We then compared Myc-associated molecular signatures between the groups in the prospective cohort after gene set enrichment analysis. The expression of c-Myc protein was assessed by immunohistochemical staining. We defined high c-Myc-immunopositivity as > 40% of bone marrow myeloblasts being c-Myc (+). Results: Significantly more Myc gene expression was found in patients who did not achieve CR by “7 + 3” induction than those who did (2439.92 ± 1868.94 vs. 951.60 ± 780.68; p = 0.047). Expression of the Myc gene and c-Myc protein were positively correlated (r = 0.495; p = 0.014). Although the non-CR group did not express more c-Myc protein than the CR group (37.81 ± 25.13% vs. 29.04 ± 19.75%; p = 0.151), c-Myc-immunopositivity could be a surrogate to predict the “7 + 3” induction chemoresponse (specificity: 81.63%). More importantly, c-Myc-immunopositivity facilitated cytogenetics to predict a “7 + 3” induction chemoresponse by increasing specificity from 91.30 to 95.92%. Conclusion: The “7 + 3” induction remains the standard of care for de novo AML patients, especially for those without a high c-Myc-immunopositivity and high-risk cytogenetics. However, different regimens might be considered for patients with high c-Myc-immunopositivity or high-risk cytogenetics.